2020
DOI: 10.1038/s41598-020-79442-4
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of autofluorescence bronchoscopy in early diagnosis of airway complications after lung transplantation

Abstract: Despite the promising results achieved so far in long-term survival after lung transplantation (LuTx), airway complications (ACs) still arise in the post-operative period. Early diagnosis and prompt treatment of ACs play a critical role in preventing their onset. Specifically, large bronchi ischemia has been recognized as a triggering factor for ACs. Autofluorescence bronchoscopy, which was first introduced for early cancer diagnosis, displays ischemic mucosae as red spots, while normal vascularized mucosae ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In contrast, early-stage treatment (≤ 6 months) was associated with a significantly higher secondary patency rate than late-stage treatment (> 6 months) (HR, 3.588; P = 0.035). The relationship between early-stage treatment and bronchial patency may be attributed to the early diagnosis and treatment of bronchial stenosis, which can affect post-procedural outcomes and the patient life expectancy [ 25 ]. This is likely because acute fibroinflammatory bronchial lesions are histologically different from mature chronic fibrosis, which occurs as long-term sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, early-stage treatment (≤ 6 months) was associated with a significantly higher secondary patency rate than late-stage treatment (> 6 months) (HR, 3.588; P = 0.035). The relationship between early-stage treatment and bronchial patency may be attributed to the early diagnosis and treatment of bronchial stenosis, which can affect post-procedural outcomes and the patient life expectancy [ 25 ]. This is likely because acute fibroinflammatory bronchial lesions are histologically different from mature chronic fibrosis, which occurs as long-term sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…However, these tissue and mucosal changes can occur in both benign bronchial lesions and malignant bronchial lesions under WLB examination, making it di cult for WLB to yield a de nitive clinical diagnosis. Thus, the ability of WLB to diagnose early mucous and submucous carcinomas is very limited, and mucosal in ammation, congestion and other factors may interfere with the nal diagnosis [30] . It has been reported that detecting preinvasive lesions using WLB is particularly di cult even for an experienced bronchoscopist, and only 29% of patients with bronchial CIS lesions were visible using WLB [31] .…”
Section: Discussionmentioning
confidence: 99%